Pengembangan Model Soal Berbasis HOTS pada Siswa Kelas V SD Negeri Pakulonan 01 Kota Tangerang Selatan - Magdalena, Ina; Nursabila, Putri Rizki; Asyifa, Syaqila Nur (MASALIQ, 2023)
This study aims to produce reliable and valid topical questions about higher order thinking skills (HOTS) that can measure the creative thinking abilities of fifth grade elementary school students and are able to explore potential impacts that will occur when students are about to work. topical HOTS questions to assess creative thinking skills. In this discussion, the research method to be used is the research and development method. In this development there are two stages of which the first stage is the introduction, the second stage is the evaluation process. And the research subjects used were 19 fifth grade students at SD Negeri Pakulonan 1. There were several data collection techniques in this study, namely tests and interviews. There are 15 HOTS thematic questions in this study to measure students' creative thinking skills including indicators of creative thinking, namely fluent thinking. Based on the results of the study, the test was declared valid because some students were able to think fluently.